PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA: Tinjauan Literatur - Ibrahim Bali Pamungkas; Muhamad Badru Zaman; Wahyu Andri Wibowo (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The aims of this research are a). to determine the effect of education and training (DIKLAT) on performance based on a literature review study, b). to determine the design that is often used in education and training research (DIKLAT) on performance, c). to find out the instruments that are often used in education and training research (DIKLAT) on performance. The method in searching for article data sources is carried out through the GARUDA database (2016-2021) to retrieve relevant articles published in Indonesian. Key terms and phrases related to education and training (DIKLAT) on performance using Literature Review abstracts or research journal texts were reviewed before being included in the review according to the criteria. Based on 10 journals over the last 5 years reviewed, the results state that education and training (DIKLAT) has a positive and significant effect on performance, and based on 10 journals over the last 5 years reviewed, the results show that the most widely used design is survey research design. based on 10 journals during the last 5 years that were reviewed the results were the most widely used instrument was the questionnaire instrument.